Machine-vision-based human-oriented mobile robots - Finžgar, Miha (Strojniški vestnik, 2017)
In this paper we present a study of vision-based, human-recognition solutions in human-oriented, mobile-robot applications. Human recognition is composed of detection, tracking and identification. Here, we provide an analysis of each step. The applied vision systems can be conventional 2D, stereo or omnidirectional. The camera sensor can be designed to detect light in the visible or infrared parts of the electromagnetic spectrum. Regardless of the method or the type of sensor chosen, the best results in human recognition can be obtained by using a multimodal solution. In this case, the vision system is enhanced with other forms of sensory information. The most common sensors are laser range finders, microphones and sonars. As medicine is expected to be one of the main fields of application for mobile robots, we give it special emphasis. An overview of current applications and proposal of potential future applications are given. Without doubt, properly controlled mobile robots will play an ever-increasing role in the future of medicine.
Keywords: algoritmi obdelave slik; medicinske aplikacije; mobilni roboti; pregledi; prepoznava človeka; strojni vid